2017
DOI: 10.3390/molecules22040602
|View full text |Cite
|
Sign up to set email alerts
|

Screening, Purification and Characterization of Anionic Antimicrobial Proteins from Foeniculum Vulgare

Abstract: Foeniculum vulgare Mill., commonly called fennel, is a medicinal plant belonging to the Umbelliferae (Apiaceae) family, and is used in traditional medicine. Antibacterial peptides were isolated using sodium phosphate citrate buffer and, for extraction, cetyltrimethyl ammonium bromide (CTAB) buffer with pH 6, have been employed and antimicrobial activity tested against four reference strains. The extracted protein was subjected to 3 kDa dialysis and separation was carried out by DEAE-ion exchange chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…New insight into the identification and characterization of novel AMPs is reported by Al Akeel et al [ 3 ]. New promising anionic antimicrobial compounds were derived from Foeniculum vulgare , a therapeutic plant belonging to the Umbelliferae (Apiaceae) family, which is widely used in traditional chinese medicine.…”
mentioning
confidence: 99%
“…New insight into the identification and characterization of novel AMPs is reported by Al Akeel et al [ 3 ]. New promising anionic antimicrobial compounds were derived from Foeniculum vulgare , a therapeutic plant belonging to the Umbelliferae (Apiaceae) family, which is widely used in traditional chinese medicine.…”
mentioning
confidence: 99%
“…We previously reported on the antimicrobial activity of anion exchange chromatography purified seed extracts from F. vulgare seed (Al Akeel et al, 2017). Preliminary examination of the active fractions suggested that one particularly potent elute fraction (# 2) was relatively non-complex with respect to the number of proteins involved and therefore appeared to be a good candidate for characterization.…”
Section: Resultsmentioning
confidence: 99%
“…Convectional protocol is used as per the manual (Agilent technologies). In brief, MS grade trypsin used in gel digestion to achieve maximum specific proteins from the gel and the procedures goes as per our previous study (Al Akeel et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The extraction and isolation procedures were as per our previous study where we have standardized our protocols for this project [ 15 ]. In brief, seed extraction was initiated by first cleaning the seeds with tap water and then distilled water to remove dirt or debris.…”
Section: Methodsmentioning
confidence: 99%